Response-Adapted Postinduction Strategy in Patients With Advanced-Stage Follicular Lymphoma: The FOLL12 Study. Issue 7 (1st March 2022) - Luminari, Stefano; Manni, Martina; Galimberti, Sara; Versari, Annibale; Tucci, Alessandra; Boccomini, Carola; Farina, Lucia; Olivieri, Jacopo; Marcheselli, Luigi; Guerra, Luca; Ferrero, Simone; Arcaini, Luca; et al.
Abstract : PURPOSE: We compared 2 years of rituximab maintenance (RM) with a response-adapted postinduction approach in patients with follicular lymphoma who responded to induction immunochemotherapy. METHODS: We randomly assigned treatment-naïve, advanced-stage, high-tumor burden follicular lymphoma patients to receive standard RM or a response-adapted postinduction approach on the basis of metabolic response and molecular assessment of minimal residual disease (MRD). The experimental arm used three types of postinduction therapies: for complete metabolic response (CMR) and MRD-negative patients, observation; for CMR and MRD-positive (end of induction or follow-up) patients, four doses of rituximab (one per week, maximum three courses) until MRD-negative; and for non-CMR patients, one dose of ibritumomab tiuxetan followed by standard RM. The study was designed as noninferiority trial with progression-free survival (PFS) as the primary end point. RESULTS: Overall, 807 patients were randomly assigned. After a median follow-up of 53 months (range, 1-92 months), patients in the standard arm had a significantly better PFS than those in the experimental arm (3-year PFS 86% v 72%; P < .001). The better PFS of the standard versus experimental arm was confirmed in all the study subgroups except non-CMR patients (n = 65; P = .274). The 3-year overall survival was 98% (95% CI, 96 to 99) and 97% (95% CI, 95 to 99) in the reference and experimental arms, respectively ( P = .238). CONCLUSION: A metabolic and molecular response-adapted therapy as assessed in the FOLL12 study was associated with significantly inferior PFS compared with 2-year RM. The better efficacy of standard RM was confirmed in the subgroup analysis and particularly for patients achieving both CMR and MRD-negative.